2021
DOI: 10.1016/j.aace.2021.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Xanthomatous Hypophysitis Presenting in An Adolescent Girl: A Long-Term Follow-Up of A Rare Case and Review of The Literature

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…Prevalence of compression symptoms reported in other studies was variable. In study by Yang et al, which included 14 patients, headache was present in 85%, visual disturbances in 71.4% compared to the study with headache as the rst symptom in 30.4% and neuro-ophthalmological disorders in 26.1% of patients [9,13]. Amano et al reported 7 patients with XG, 6 secondary to RCC, with high prevalence of headache 86%, visual disturbances 71% and hypopituitarism 86% [10].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Prevalence of compression symptoms reported in other studies was variable. In study by Yang et al, which included 14 patients, headache was present in 85%, visual disturbances in 71.4% compared to the study with headache as the rst symptom in 30.4% and neuro-ophthalmological disorders in 26.1% of patients [9,13]. Amano et al reported 7 patients with XG, 6 secondary to RCC, with high prevalence of headache 86%, visual disturbances 71% and hypopituitarism 86% [10].…”
Section: Discussionmentioning
confidence: 93%
“…In our study only one patient was diagnosed with XH while majority had pituitary XG (5 primary, 8 secondary). So far 36 case reports of XH have been published in the literature [12,13], the largest case series included 12 patients with XH [4].…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 17 , 21 In one case observed by Deodhare et al, 18 corticosteroid therapy temporarily shrunk an XH lesion; however, the lesion significantly expanded following discontinuation of the therapy. In another report by Wong et al, 15 a 14-year-old female with XH experienced gradually increasing size of her sellar mass for 2 years following partial resection, at which point she was treated with high-dose prednisolone. A significant reduction in the mass size was demonstrated 6 months later as a response to the steroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Observations Xanthomatous lesions of the pituitary gland are a rare category of hypophysitis that have been described in several reports. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Traditionally, these lesions have been divided into two distinct categories: XH and XG; however, there is growing evidence of clinicopathologic overlap between them. 3 XH is histologically characterized by the presence of foamy histiocytes and lymphoplasmacytic infiltrates within the pituitary gland or sellar region with little to no hemosiderin pigment.…”
Section: Discussionmentioning
confidence: 99%